[68Ga]Ga-PSMA PET/MRI, histological PSMA expression and preliminary experience with [177Lu]Lu-PSMA therapy in relapsing high-grade glioma - Truckenmueller, Peter; Graef, Josefine; Scheel, Michael; Vajkoczy, Peter; Capper, David; Kaul, David; Furth, Christian; Amthauer, Holger; Brenner, Winfried; Onken, Julia Sophie (Frontiers in Oncology, 2022)
High-grade gliomas (HGG) are still associated with a dismal prognosis. Prostate specific membrane antigen (PSMA) is discussed as a theranostic target for PSMA-directed radioligand therapy ([177Lu]Lu-PSMA RLT). Here, we report on the correlation of [68Ga]Ga-PSMA uptake with histological PSMA expression and on our preliminary experience with [177Lu]Lu-PSMA therapy in relapsing HGG. Patients with relapsing HGG underwent [68Ga]Ga-PSMA PET/MRI to evaluate eligibility for an individualized treatment approach with [177Lu]Lu-PSMA. Standard uptake values (SUV) for tumor and liver and respective tumor-to-background ratios (compared to the liver) (TBR) on [68Ga]Ga-PSMA PET/MRI were assessed. Eligibility criteria for [177Lu]Lu-PSMA therapy were exhaustion of all standard treatment options available and TBRmax>1.0. In 11 samples, immunohistochemical PSMA expression was determined, quantified using the H-score and correlated with uptake on [68Ga]Ga-PSMA PET/MRI. We included 20 patients with a median age of 53 years (IQR 42-57). The median SUV on [68Ga]Ga-PSMA PET/MRI was 4.5 (3.7-6.2) for SUVmax and 1.4 (1.1-1.7) for SUVmean. The respective TBR was maximum 0.6 (0.4-0.8) and mean 0.3 (0.2-0.4). High TBRmax correlated with increased endothelial PSMA expression [H-score of 65 (62.5-77.5)]. Three patients (15%) presented a TBRmax>1.0 and qualified for [177Lu]Lu-PSMA therapy. No treatment related toxicity was observed. Only a minority of patients with relapsing HGG qualified for [177Lu]Lu-PSMA therapy. Our data demonstrates that PSMA expression in the neo-vasculature corresponds to PSMA uptake on [68Ga]Ga-PSMA PET/MRI and might be used as a screening tool for patient selection. Future prospective studies need to focus the debate on TBRmax thresholds as inclusion criteria for PSMA RLT.